Multifaceted Aspects of Dysfunctional Myelopoiesis in Cancer and Therapeutic Perspectives with Focus on HCC - Andrea Arleo; Annapaola Montagner; Catia Giovannini; Fabrizia Suzzi; Fabio Piscaglia; Laura Gramantieri (Biomolecules)
Myelopoiesis provides for the formation and continued renewal of cells belonging primarily to the innate immune system. It is a highly plastic process that secures the response to external and internal stimuli to face acute and changing needs. Infections and chronic diseases including cancer can modulate it by producing several factors, impacting proliferation and differentiation programs. While the lymphocytic compartment has attracted major attention due to the role of adaptive immunity in anticancer immune response, in recent years, research has found convincing evidence that confirms the importance of innate immunity and the key function played by emergency myelopoiesis. Due to cancer’s ability to manipulate myelopoiesis to its own advantage, the purpose of this review is to outline myelopoiesis processes within the tumor microenvironment and suggest possible therapeutic lines of research to restore the physiological functioning of the host’s immune system, with a special outlook on hepatocellular carcinoma (HCC).